2011
DOI: 10.1289/ehp.1003326
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Genes Downstream of TLR4 Signaling after Ozone Exposure in Mice: A Role for Heat-Shock Protein 70

Abstract: Background: Toll-like receptor 4 (TLR4) is involved in ozone (O3)-induced pulmonary hyperpermeability and inflammation, although the downstream signaling events are unknown.Objectives: The aims of our study were to determine the mechanism through which TLR4 modulates O3-induced pulmonary responses and to use transcriptomics to determine potential TLR4 effector molecules.Methods: C3H/HeJ (HeJ; Tlr4 mutant) and C3H/HeOuJ (OuJ; Tlr4 normal) mice were exposed continuously to 0.3 ppm O3 or filtered air for 6, 24, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 49 publications
3
45
0
Order By: Relevance
“…Williams and colleagues identified 400 differentially expressed genes (greater than twofold) in BALB/c mice 3 hours after ozone exposure, and also identified a number of markers of inflammation as the most affected genes (44). Bauer and colleagues profiled C3H/ HeJ and C3H/HeOuJ mice to identify ozone candidate genes downstream of TLR4, and demonstrated a role for heat shock protein-70 (32). Our analysis of gene expression in the lung after ozone exposure differs from these previously published studies because it focused on the priming effect of ozone on innate immunity.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Williams and colleagues identified 400 differentially expressed genes (greater than twofold) in BALB/c mice 3 hours after ozone exposure, and also identified a number of markers of inflammation as the most affected genes (44). Bauer and colleagues profiled C3H/ HeJ and C3H/HeOuJ mice to identify ozone candidate genes downstream of TLR4, and demonstrated a role for heat shock protein-70 (32). Our analysis of gene expression in the lung after ozone exposure differs from these previously published studies because it focused on the priming effect of ozone on innate immunity.…”
Section: Discussionmentioning
confidence: 94%
“…Previously, the increase in the response of TLR4 to ozone alone was determined to be a result of the ozone-induced release of endogenous ligands (hyaluronan and heat-shock proteins) that stimulate TLR4, resulting in the migration of TLR4 to the surface of the cell (31). A subsequent gene expression profiling study by another group showed that heat-shock protein-70 is an effector molecule downstream of TLR4, and is involved in the regulation of ozone-induced lung inflammation by triggering pathways similar to those of TLR4 (32). This is likely a general mechanism that acts on all TLRs and accounts for the increases of TLR1 and TLR2 in response to ozone alone in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two transcription factors induce upregulation of effector molecules and interferon (IFN)-inducible genes, such as IFN-gamma-induced protein 1 and IFN-β. 81,84,87 TLR signaling can be initiated through the interaction of numerous exogenous and endogenous ligands specific to a wide variety of TLRs. As detailed in Table 1, exogenous ligands include viruses and cell wall components of Grampositive and Gram-negative bacteria such as bacterial endotoxin/lipopolysaccharide, a well known inflammatory agent.…”
Section: Tlr Structure and Functionmentioning
confidence: 99%
“…87,94 However, the gaseous nature of O 3 means that an alternate mechanism is likely responsible for TLR involvement in O 3 -induced inflammation. Although TLR2 and TLR4 have been studied as noted in the aforementioned studies, future research is needed to define the role of the remaining TLRs (TLR1, TLR3, TLR5-12) in air pollution-induced injury and disease.…”
mentioning
confidence: 99%